1992
DOI: 10.1111/j.1471-4159.1992.tb08350.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the Vulnerability of Neurons in the Substantia Nigra of Patients with Parkinson's Disease Related to Their Neuromelanin Content?

Abstract: The contribution of neuromelanin (NM) to the pathogenesis of Parkinson's disease (PD) has long been suspected. In particular, a correlation has been reported between the estimated cell loss in the mesencephalic dopaminergic cell groups and the percentage of NM-pigmented neurons in these cell groups. To test whether the amount of pigment per cell is a critical factor or whether the presence of NM within a neuron is sufficient to account for the degeneration of dopaminergic neurons, the NM content was measured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
133
0
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(143 citation statements)
references
References 21 publications
8
133
0
2
Order By: Relevance
“…It should be noted that A9 dopaminergic neurons, which contain a high level of α-Syn (48,49) and increased pigmentation by neuromelanin in the early stage of PD before producing Lewy bodies (12,50,51), exhibit early vulnerability. Analysis of brain samples from PD patients showed that the optical density of neuromelanin increased together with α-Syn accumulation around the neuromelanin granules in A9 neurons (51), and α-Syn was found to be a major proteic component, cross-linked to neuromelanin from brains of PD patients (52).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that A9 dopaminergic neurons, which contain a high level of α-Syn (48,49) and increased pigmentation by neuromelanin in the early stage of PD before producing Lewy bodies (12,50,51), exhibit early vulnerability. Analysis of brain samples from PD patients showed that the optical density of neuromelanin increased together with α-Syn accumulation around the neuromelanin granules in A9 neurons (51), and α-Syn was found to be a major proteic component, cross-linked to neuromelanin from brains of PD patients (52).…”
Section: Discussionmentioning
confidence: 99%
“…Interest in this pigment has seen a resurgence in recent years because of a hypothesized link between NM and the especial vulnerability of NM-containing neurons of the substantia nigra pars compacta (SN) for cell death in Parkinson disease (PD) (2,3). In particular, the interaction between iron and NM has been a focus of research (4 -8) because a marked accumulation of iron related to disease severity is reported in the parkinsonian SN (9 -11).…”
Section: Neuromelanin (Nm)mentioning
confidence: 99%
“…In both of these regions of the human brain, the neuromelanin concentration normally increases linearly with age. In Parkinson's disease, the tissue concentration of neuromelanin decreases dramatically because DA pigmented neurons are preferentially lost compared with nonpigmented ones (3,4). Reduced neuronal content of neuromelanin in substantia nigra has been reported in patients with Parkinson's disease (3), Alzheimer's disease (5), and Rett syndrome (6).…”
mentioning
confidence: 99%